Dinamika Spasial Tanah Terdaftar dan Implikasinya terhadap Sistem Penghidupan Masyarakat Lokal di Kabupaten Takalar - Rini Ariani Amir; Baba Barus; Endriatmo Soetarto (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2020)
Spatial Dynamic of Registered Land and Its Implications to the Livelihood System of Local Communities in Takalar Regency Takalar Regency is part of the Mamminasata Urban Region in South Sulawesi Province, which is designed to accelerate regional economic growth . Therefore, the government needs to make efforts to create a conducive investment climate in Takalar Regency. One of effort was by accelerating land registration through the Systematic and Complete Land Registration Program (PTSL). PTSL has been implemented in Takalar Regency since 2017. This research aims to identify the spatial dynamic of land registered in Takalar Regency and analyze its implications to the livelihood system of local communities. Data of land registered were analyzed by descriptive analysis, overlaid, and Moran Index spatial autocorrelation analysis was conducted to identify spatial dynamics. Data of livelihoods system, i.e. the human capital, natural capital, social capital, physical capital, and financial capital, were analyzed by Score Index method. Purposive sampling was applied to three village typologies, namely the developing coastal village, the independent coastal village, and the developing non-coastal village. The result shows that unp to 2019, 55% of the number of land parcels in Takalar Regency had been registered. Registered land had increased by 11% from 2017 and PTSL had contributed 54% of the increase. The ratio of land registered to the number of land parcels in 29 villages had changed and showed a random spatial distribution pattern dominated in northwest areas of the regency. The spatial dynamics of land registered were also followed by the dynamics of land transactions, land values, and land conversion. The result of the Scoring Index method showed that the livelihood capital of local communities after implementation of PTSL was categorized as sufficient for all typologies of sample villages. Land registration had direct implications for natural capital and financial capital.